(untitled) (Scientific journal of the Fergana State University, 2024)
The article explores the passion of King and poet Zahiriddin Muhammad Babur for literary works of the past, especially for the works of poets of Persian and Tajik literature. The author, relying on the Persian poetry of “Boburnoma”, tried to embody the influence of Bobur from the poetry of the poets of Porzigou by way of comparison and reflect the literary ties of the Tajik-Uzbek peoples in this context.